Rosaries and Statues: Mediating Divine Intervention in Bougainville, Papua New Guinea - Anna-Karina Hermkens (Religions, 2021)
In the Autonomous Region of Bougainville (ARoB) in Papua New Guinea, the changes of Vatican II led to significant Church reform, creating “Liklik Kristen Komuniti” (small Christian communities) that gave more responsibility to the laity. Moreover, as elsewhere in the world, Charismatic Catholicism was introduced and embraced. At the same time, private devotions, and in particular devotions to Mary, became immensely popular and powerful in Bougainville. This is partly due to the Bougainville crisis (1988–1998), which caused immense suffering, but also triggered a surge in popular devotions as people looked for spiritual guidance to deal with the hardships of the crisis. This paper shows how in the context of social and economic upheaval, charismatic popular devotions became increasingly influential with rosaries and statues becoming important mediums in facilitating healing and socio-political renewal. This shows the strength of popular devotions and the importance of material religion in particular. It also elucidates how popular devotions in Bougainville are part of global Catholic developments, as well as transnational practices that place Mary in the center of devotional practices.